2019
DOI: 10.1111/1462-2920.14633
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical diversity of glycosphingolipid biosynthesis as a driver of Coccolithovirus competitive ecology

Abstract: Summary Coccolithoviruses (EhVs) are large, double‐stranded DNA‐containing viruses that infect the single‐celled, marine coccolithophore Emiliania huxleyi. Given the cosmopolitan nature and global importance of E. huxleyi as a bloom‐forming, calcifying, photoautotroph, E. huxleyi–EhV interactions play a key role in oceanic carbon biogeochemistry. Virally‐encoded glycosphingolipids (vGSLs) are virulence factors that are produced by the activity of virus‐encoded serine palmitoyltransferase (SPT). Here, we charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 67 publications
3
20
0
Order By: Relevance
“…With the increased use of state-of-the-art single-cell and single-virus genomics approaches in virus ecology, use of single-cell viral infection-dynamics visualisation methods, and efforts to link mechanistic understanding from laboratory experiments to larger scale field observations of hostvirus interactions (Allers et al, 2013;Ku et al, 2020;Nissimov et al, 2019), it is likely that the number of studies using virus isolates from private collections (Table 1) will increase. At the same time, the microbiology field in general is also recognising that many studies across the different sub-disciplines can benefit from standardisation of protocols and common analytical frameworks (Thompson et al, 2017), improving the reproducibility of studies, and the way key findings are being reported.…”
Section: An Aquatic Virus Culture Collection Will Allow For Increasedmentioning
confidence: 99%
See 2 more Smart Citations
“…With the increased use of state-of-the-art single-cell and single-virus genomics approaches in virus ecology, use of single-cell viral infection-dynamics visualisation methods, and efforts to link mechanistic understanding from laboratory experiments to larger scale field observations of hostvirus interactions (Allers et al, 2013;Ku et al, 2020;Nissimov et al, 2019), it is likely that the number of studies using virus isolates from private collections (Table 1) will increase. At the same time, the microbiology field in general is also recognising that many studies across the different sub-disciplines can benefit from standardisation of protocols and common analytical frameworks (Thompson et al, 2017), improving the reproducibility of studies, and the way key findings are being reported.…”
Section: An Aquatic Virus Culture Collection Will Allow For Increasedmentioning
confidence: 99%
“…For instance, it is work with virus isolates in the laboratory that elucidated the role of virus-derived glycosphingolipids in terminating coccolithophore blooms and the rate-limiting biochemical steps in this process (Han et al, 2006;Vardi et al, 2012Vardi et al, , 2009, the competitive interactions between different coccolithoviruses (i. e., viruses infecting the E. huxleyi microalga) over the host for infection and the use of glycosphingolipid as virulence factors affecting viral success (Nissimov, Napier, Allen, & Kimmance, 2016;Nissimov et al, 2019), autophagy pathways in E. huxleyi during infection (Schatz et al, 2014), the virus strain-specific variations with regards to the induction of polysaccharide production in infected E. huxleyi cells (Nissimov et al, 2018), and the role of diatom-infecting viruses in aggregating material into sinking particles, important to the carbon biogeochemistry of the ocean (Yamada et al, 2018). Other notable examples where aquatic virus isolates were used to shed light on putative functions include the discovery of auxiliary metabolic genes (AMGs) in marine cyanophages (Breitbart, 2012), chlorovirus genes involved in carbohydrate metabolism (Van Etten et al, 2017), and genes involved in the production of fibers in Mimiviruses (Sobhy, La Scola, Pagnier, Raoult, & Colson, 2015).…”
Section: Classifying Cataloguing and Preserving Viruses Has An Unexpmentioning
confidence: 99%
See 1 more Smart Citation
“…The cosmopolitan coccolithophore Emiliania huxleyi and its Coccolithoviruses (EhVs) are one of the central models of virulent dynamics. This virus-host system has provided critical insight into the subcellular molecular controls, global biogeochemical impacts, and ecosystem outcomes of virulent infection in terminating phytoplankton blooms [25][26][27][28][29][30][31][32][33][34][35] . Like other phytoplankton-virus systems, virulence in the E. huxleyi-EhV system has been supported by laboratory-and environmental-based studies showing lysis of hosts at high host densities or bloom climax that are matched by predictions from virulent-only theoretical models.…”
mentioning
confidence: 99%
“…Recent work has shown the dominance of more-virulent phytoplankton viruses in the laboratory and less-virulent viruses in the environment 28 . Building on this observation, we sought to determine if the "rules of infection" in the E. huxleyi-EhV system were conserved across nutrient-enriched laboratory and mesocosm conditions with host densities of~10 5 -10 6 cells per milliliter and environmental conditions with densities of ≤10 3 cells per milliliter.…”
mentioning
confidence: 99%